Kinetics of Bovine leukemia virus aspartic protease reveals its dimerization and conformational change. - Martín Fló; Federico Carrión; Natalia Olivero-Deibe; Sergio Bianchi; Madelón Portela; Florencia Rammauro; Beatriz Alvarez; Otto Pritsch (PLoS ONE)
The retropepsin (PR) of the Bovine leukemia virus (BLV) plays, as in other retroviruses, a crucial role in the transition from the non-infective viral particle to the infective virion by processing the polyprotein Gag. PR is expressed as an immature precursor associated with Gag, after an occasional -1 ribosomal frameshifting event. Self-hydrolysis of PR at specific N- and C-terminal sites releases the monomer that dimerizes giving rise to the active protease. We designed a strategy to express BLV PR in E. coli as a fusion protein with maltose binding protein, with a six-histidine tag at its N-terminal end, and bearing a tobacco etch virus protease hydrolysis site. This allowed us to obtain soluble and mature recombinant PR in relatively good yields, with exactly the same amino acid composition as the native protein. As PR presents relative promiscuity for the hydrolysis sites we designed four fluorogenic peptide substrates based on Förster resonance energy transfer (FRET) in order to characterize the activity of the recombinant enzyme. These substrates opened the way to perform kinetic studies, allowing us to characterize the dimer-monomer equilibrium. Furthermore, we obtained kinetic evidence for the existence of a conformational change that enables the interaction with the substrate. These results constitute a starting point for the elucidation of the kinetic properties of BLV-PR, and may be relevant not only to improve the chemical warfare against this virus but also to better understand other viral PRs.